Whether Erythropoietin can be a Neuroprotective Agent against Premature Brain Injury: Cellular Mechanisms and Clinical Efficacy - Ma, Xueling; Shi, Yuan (Current Neuropharmacology, 2022)
Preterm infants are at high risk of brain injury. With more understanding of the preterm brain injury's pathogenesis, neuroscientists are looking for more effective methods to prevent and treat it, among which erythropoietin (Epo) is considered as a prime candidate. This review tries to clarify the possible mechanisms of Epo in preterm neuroprotection and summarize updated evidence considering Epo as a pharmacological neuroprotective strategy in animal models and clinical trials. To date, various animal models have validated that Epo is an anti-apoptotic, antiinflammatory, anti-oxidant, anti-excitotoxic, neurogenetic, erythropoietic, angiogenetic, and neurotrophic agent, thus preventing preterm brain injury. However, although the scientific rationale and preclinical data for Epo's neuroprotective effect are promising, when translated to bedside, the results vary in different studies, especially in its long-term efficacy. Based on existing evidence, it is still too early to recommend Epo as the standard treatment for preterm brain injury.
Keywords: perinatal neuroinflammation